2007
DOI: 10.1302/0301-620x.89b12.19481
|View full text |Cite
|
Sign up to set email alerts
|

The long-term results of endoprosthetic replacement of the proximal tibia for bone tumours

Abstract: We have investigated whether improvements in design have altered the outcome for patients undergoing endoprosthetic replacement of the proximal tibia following resection of a tumour. Survival of the implant and 'servicing' procedures have been documented using a prospective database. A total of 194 patients underwent a proximal tibial replacement, with 95 having a fixed-hinge design and 99 a rotating-hinge with a hydroxyapatite collar; their median age was 21.5 years (10 to 74). At a mean follow-up of 14.7 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
142
0
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 45 publications
14
142
0
13
Order By: Relevance
“…Importantly, two-stage revision surgery and even amputation were not necessary in any of the patients in the silver group, whereas these procedures were almost always performed in the titanium group. The literature also includes many studies describing a high percentage of two-stage revision surgery or even amputation in 19-46% of cases [5][6][7]27]. As in the present study, Jeys et al [6] and Myers et al [7] also found that the risk for secondary amputation due to infection was highest in proximal tibia replacements.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Importantly, two-stage revision surgery and even amputation were not necessary in any of the patients in the silver group, whereas these procedures were almost always performed in the titanium group. The literature also includes many studies describing a high percentage of two-stage revision surgery or even amputation in 19-46% of cases [5][6][7]27]. As in the present study, Jeys et al [6] and Myers et al [7] also found that the risk for secondary amputation due to infection was highest in proximal tibia replacements.…”
Section: Discussionsupporting
confidence: 71%
“…Despite advances in endoprosthetic design that have led to lower complication rates, particularly with regard to mechanical failure and aseptic loosening [1], periprosthetic infection of megaprostheses continues to be a common and serious complication in orthopedic oncology [5][6][7]. Currently, it is not possible to avoid periprosthetic infection completely, despite the use of systemic antibiotic treatment, operating rooms with laminar airflow, and routine screening for methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations